2020
DOI: 10.1002/adfm.202001607
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Lithium‐Ion Conductive Li2S/Li2Se Protection Layer for Stable Lithium Metal Anode

Abstract: Constructing artificial solid‐electrolyte interphase (SEI) on the surface of Li metal is an effective approach to improve ionic conductivity of surface SEI and buffer Li dendrite growth of Li metal anode. However, constructing of homogenous ideal artificial SEI is still a great challenge. Here, a mixed lithium‐ion conductive Li2S/Li2Se (denoted as LSSe) protection layer, fabricated by a facile and inexpensive gas–solid reaction, is employed to construct stable surface SEI with high ionic conductivity. The Li2S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
135
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(137 citation statements)
references
References 50 publications
2
135
0
Order By: Relevance
“…These characterizations confirmed that the composition of the layer could be Li 2 Se 2 /Li 2 Se, which could enhance the cycling performance of the Li–Se batteries. This result is consistent with the previously reported literature 58 . Furthermore, EIS spectra were recorded at open-circuit voltage before cycling and after 1st cycle, 2nd cycle, 5th cycle, 10th cycle and 50th cycle at 0.1 C (Supplementary Fig.…”
Section: Resultssupporting
confidence: 94%
“…These characterizations confirmed that the composition of the layer could be Li 2 Se 2 /Li 2 Se, which could enhance the cycling performance of the Li–Se batteries. This result is consistent with the previously reported literature 58 . Furthermore, EIS spectra were recorded at open-circuit voltage before cycling and after 1st cycle, 2nd cycle, 5th cycle, 10th cycle and 50th cycle at 0.1 C (Supplementary Fig.…”
Section: Resultssupporting
confidence: 94%
“…Additionally, the Li 2 Se-rich SEI film offers high mechanical and chemical stability, preventing Li dendrite growth. [40] The surface SEM images in Figure 3a,b demonstrate that CoSe@C is uniformly covered with a thin layer of Li after plating 2 mA h cm −2 Li. The cross-sectional SEM image Figure 1.…”
Section: Resultsmentioning
confidence: 97%
“…[ 135 ] As most of the Li–S studies involved use of an excessive amount of Li on the anode side, the chemical incompatibility between Li anode and liquid electrolyte that are rarely discussed yet are equally important. Various strategies, such as high‐salt‐concentration electrolytes [ 136 ] and artificial SEI layer, [ 137 ] are expected to manipulate the electrolyte chemistry and stabilize the anode–electrolyte interface. In addition to the anode compatibility, the use of flammable liquid electrolytes may also involve safety concerns and leakage hazards.…”
Section: Conclusion and Prospectivementioning
confidence: 99%